A grounded theory approach to the development of a framework for researching children’s decision-making skills within design and technology education - Mettas, Alexandros; Norman, Eddie (Design and Technology Education: An International Journal, 2011)
This paper discusses the establishment of a framework for researching children’s decision-making skills in design and technology education through taking a grounded theory approach. Three data sources were used: analysis of available literature; curriculum analysis and interviews with teachers concerning their practice in relation to their respective national curricula; and a study of classroom activity in order to gather children’s’ perspectives. These three data sources provided triangulation, as well as supporting the validation of the data obtained. The main areas of interest for the literature search were children’s decision-making strategies, the implementation of decision-making in educational contexts and the roles of teachers and curriculum materials in the development of children’s decision-making skills. In this paper the key outcomes of this literature search are presented. Teachers in Cyprus, England and Iceland, were interviewed concerning their practice and the results of these interviews are presented. The exploratory study was conducted in a Cypriot classroom and the results found in this context are noted and compared with the literature sources and interview outcomes. The resulting framework illustrates the possible factors that affect children’s decision-making skills within design and technology education and is designed to be used in a subsequent research investigation using these possible factors as preset codes.